Anatomy of vegetative organs and inflorescence axis of Orectanthe sceptrum (Xyridaceae-Poales) - Gonzaga de Oliveira, Fernanda Martins [UNESP]; Scatena, Vera Lucia [UNESP]; Oriani, Aline [UNESP] (Torrey Botanical Soc, 2015)
Xyridaceae comprise two subfamilies: Xyridoideae and Abolbodoideae, which are morphologically distinct. Orectanthe belongs to Abolbodoideae and comprises two species with restricted distribution. The anatomy of root, stem, leaf, and inflorescence axis of Orectanthe sceptrum was studied aiming to characterize the species in a comparative approach. The anatomy of the roots is first described here for the genus and they are characterized by presenting two distinct patterns according to their developmental stage and function. Intracellular papillae were observed in the epidermal and cortical cells, increasing the root absorption surface. These papillae are exclusive of O. sceptrum within the family as well as the following characteristics: epidermal cells with thickened outer periclinal walls in the stem, epidermal cells with U-shaped thickened walls in the leaf blade, and chlorenchyma with arm cells in both the leaf blade and inflorescence axis. Orectanthe shares with Abolboda an indistinct endodermis in the stem and a hypodermis beneath both leaf surfaces and in the inflorescence axis. A continuous pericycle in the root, stomata restricted to the abaxial surface of the leaf blade, vascular bundles with sheath extensions distributed in a single row in the mesophyll, and large lacunae in the leaf sheath are features shared by Orectanthe, Abolboda, and Aratitiyopea, characterizing Abolbodoideae. A great similarity was observed between Abolbodoideae and Eriocaulaceae, as both have roots with heterogeneous cortex and continuous pericycle, and bifacial, hypostomatic leaves presenting hypodermis and vascular bundles with sheath extensions.
Keywords: anatomy; leaf; Orectanthe; root; scape; stem; Xyridaceae